THE DECISION TO PURCHASE BEVERAGES IN MALANG: STUDY AT DAUN TEA BAR - Sudjoni, M. Noerhadi; Khoiriyah, Nikmatul; Yunizar, Nila; Sari, Dina Kartika (Journal of Agricultural Socio-Economics (JASE), 2023)
Indonesia has a high potential for tea production, so it is very popular with young people, as shown by data on the share of Indonesian household expenditure on food and beverages, which is the second largest after grains. This research aims to analyze the purchasing factors of Daun Tea Bar drink. The research was conducted in Malang using primary data collected by distributing questionnaires through Google Forms. The research sample was determined by Accidental Sampling of as many as 56 consumers. Data analysis using Logit model regression. The results showed that Daun Tea Bar consumers were dominated by students (46.4%), Private Employees (5.4%), Entrepreneurs (1.8%), and Others (1.8%) purchasing models of  Daun Tea Bar drinks in Malang are influenced by 12 variables, namely income, occupation, lifestyle, tastes, product quality, Daun tea bar drink prices, prices of other drinks, place, promotion, people, process, physical appearance. Knowing the lifestyle of consumers, the cost of Daun Tea Bar drinks is lower, the prices of other drinks are higher, the place is comfortable, and the manufacturing process is precise and fast, significantly increasing the purchase of Daun Tea Bar drinks. Meanwhile, income, occupation, taste, product quality, promotion, people, and physical appearance have no effect. This finding confirms that the lifestyle of young people or the people of Malang towards the consumption of beverages is quite high.